IMPACT OF CUSTOMERS’ BUYING DECISIONS TOWARDS MOBILE PHONE AT PERAMBALUR TOWN - SAKTHIVEL, R.; Kalaiselvan, Dr.D. (IJRDO - Journal of Applied Management Science, 2017)
Mobile phone has diverse usages to different users in accordance with their necessities.With dramatic increase in mobile phone usage in recent years, people take into account variousfactors while they decide purchasing a mobile phone. This study has put efforts to uncover theunderlying factors those affect customers in choosing mobile phone. Data were collected fromthose people live in Khulna city maintaining equal ratios of various groups like male, female,businessmen, employees, students and others (mostly housewives). To select desired respondents,convenient sampling method was used. A structured questionnaire designed based on previousstudy with five point Likert scale was used to interview respondents. Factor analysis was appliedto extract the underlying factors affect mobile phone purchasing decision. The results show thatthe most important factor is physical attributes. Some other factors are pricing, charging andoperating facilities, size and weight, friends’ and colleagues’ recommendations, neighbors’recommendations and advertising.